2002
DOI: 10.1037/0735-7044.116.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in negative patterning, but not simple discrimination learning, in rats with 192 IgG-saporin lesions of the nucleus basalis magnocellularis.

Abstract: Rats with 192 IgG-saporin lesions of the nucleus basalis magnocellularis (NBM) and sham-operated rats were trained in either a simple discrimination paradigm assessing simple association learning or a negative patterning paradigm assessing configural association learning. In the simple discrimination task, rats were reinforced for responding to a light but were not reinforced for responding to a tone. In the negative patterning discrimination task, rats were reinforced for responding to either a light or a ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
(149 reference statements)
2
16
1
Order By: Relevance
“…Consistent with these results, the LS is positioned at an essential node point for integrating cognitive information from the various brain regions, including the prefrontal cortex, and relaying it to diencephalic and mesencephalic regions to directly control behavioral responses (Sheehan et al, 2004). Furthermore, the LS and MS have reciprocal connections with the nucleus of basalis of Meynert (substantia innominata; Lamour et al, 1984), which is involved in negative patterning similar to that (Tone1 + Light1) in the present study (Butt et al, 2002). Taken together, the existence of CS 0 -related neurons in the LS suggests that cognitive information from the prefrontal cortex and the nucleus of basalis of Meynert may exert inhibitory control on emotional and motivational behaviors through the LS.…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with these results, the LS is positioned at an essential node point for integrating cognitive information from the various brain regions, including the prefrontal cortex, and relaying it to diencephalic and mesencephalic regions to directly control behavioral responses (Sheehan et al, 2004). Furthermore, the LS and MS have reciprocal connections with the nucleus of basalis of Meynert (substantia innominata; Lamour et al, 1984), which is involved in negative patterning similar to that (Tone1 + Light1) in the present study (Butt et al, 2002). Taken together, the existence of CS 0 -related neurons in the LS suggests that cognitive information from the prefrontal cortex and the nucleus of basalis of Meynert may exert inhibitory control on emotional and motivational behaviors through the LS.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, Butt and co-workers have reported that either excitotoxic lesions of the NBM, or selective cholinergic lesions of the NBM using 192IgG-SAP, can significantly impair acquisition of a negative patterning task, without producing impairment on a similar transverse patterning task (Butt and Bowman, 2002;Butt and Hodge, 1997;Butt, Noble, Rogers, and Rea, 2002). There are several possible explanations for the disagreement between these results.…”
Section: Effects On Ca Acquisitioncontrasting
confidence: 45%
“…These capacities are acquired during development as a result of synaptic maturation in the sensory circuit and can be improved by training in adulthood (Sanes and Woolley, 2011). Lesions of cortical cholinergic fibers can result in decreased detection, identification, and localization of stimuli and impaired learning, storage, and flexible retrieval of sensory associations (Berger-Sweeney et al, 2000; Butt et al, 2002; Cabrera et al, 2006; Leach et al, 2013; Vale-Martinez et al, 2002). …”
Section: Improving Perception By Manipulating Neuromodulationmentioning
confidence: 99%